Nanotech for Crop Protection: Utilizing Nanoparticles for Targeted Pesticide Delivery - Rathore, Ashish; Hasan , Wajid; Ramesha N M; Pujar, Kishor; Singh, Rajan; Panotra , Narinder; Satapathy , Satya Narayan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The use of pesticides plays a vital role in agriculture for protecting crops from pests and diseases. However, conventional delivery methods have drawbacks including toxicity, lack of efficiency, and negative environmental impacts. Nanotechnology offers solutions through nano-enabled smart pesticide delivery systems. These utilize nanoparticles as carriers that can encapsulate, absorb, or bind pesticides. Nanoparticles like liposomes, polymer nanoparticles, dendrimers, nanoemulsions, and nanocapsules allow for targeted and controlled release directly onto crops and pests. This improves pesticide efficacy while reducing toxicity and leakage into soil and water systems. Additional functionalization of nanoparticles can also improve targeting, uptake, and controlled environmental release. Examples include using ligands for binding to plant surfaces and pH-responsive nanoparticles that release pesticides following uptake by pests. The use of nanotechnology allows minimal use of pesticides, reducing environmental contamination and exposure risks. Challenges remain such as higher costs,Scaling up fabrication, assessing ecological impacts, and lack of standardized regulations. Further research and development of nano-enabled pesticide delivery can pave the way for next-generation crop protection solutions.